Efeitos da exposição por quinze dias ao tributilestanho (500 ng/kg) sobre a reatividade e morfologia da aorta de ratas - Ximenes, Carolina Falcão (2016)
The tributyltin chloride (TBT) is a chemical that causes a reduction of serum estrogen (E2) levels and may cause endocrine disruption and toxic effects in mammals. The dose of 500 ng/kg was used to be found in the environment, thus mimicking a human exposure to a realistic concentration. However is not well understood. The objective of this study was to investigate the effects of exposure of 500 ng/kg of TBT for fifteen days on vascular reactivity, and the possible relationship between vascular abnormalities as a result of the development of oxidative stress. Female Wistar rats were used (250-300 g), divided into control group and exposed to TBT (500 ng/kg) daily by gavage. The E2 level in the serum was analyzed by radioimmunoassay and lipid peroxidation was measured in the aorta using the level of substances reactive to thiobarbituric acid (TBARS). Aortic rings vascular reactivity incubated with KCl (75 mM), immediately after, with phenylephrine (10-10 – 3 x 10-4 M) was assessed in the presence (E+) and absence of the endothelium (E-). To analyze the possible factors involved in endothelial effect of TBT were carried concentrationresponse curves to phenylephrine with L-N G -Nitroarginine methyl ester (L-NAME) (100 µM), apocynin (30 µM), superoxide dismutase (SOD) 150 (U/ml), Catalase (1000 U/ml), Tiron (1 mM) and allopurinol (100 µM). The relaxation response endothelium-induced was evaluated by acetylcholine-induced relaxation curve (ACh 10-10 – 3 x 10-4 M), and the relaxation response mediated by the vascular smooth muscle was tested by curve sodium nitroprusside (SNP, 10-11 – 3 x 10- 7 M) in arteries pre-contracted with phenylephrine (10-6 M). To analyze the production of superoxide anion "in situ" was used dihydroethidium (DHE). The structural integrity of the aorta was evaluated by staining hematoxyline and eosin, Pricosirius Red and by scanning electron microscopy (SEM). Data were expressed as mean ± SEM. Statistical analysis used Student's t test unpaired and ANOVA 1 way for evaluate the production of O2 •- “in situ”, with p < 0.05 considered statistically significant. The oestrogen level in serum (Control: 32.2 ± 6.6; TBT: 19.95 ± 2.3 pg/ml, n=4, p < 0.05) was decreased 38 % and the lipid peroxidation (Control: 7.53 ± 1.26; TBT: 12.33 ± 0.81 nmol/mg protein n=3-5, p < 0.01) was higher in the TBT group. The response to KCl (Controle: 2.34 ± 0.06; TBT: 3.48 ± 0.17 g, n=10, p < 0.01) and the response to phenylephrine (Emax, Control: 1.54 ± 0.09; TBT: 4.01 ± 0.36 g, n=10, p < 0.01; pD2, Control: -6.32 ± 0.09; TBT: -6.85 ± 0.14 g, n=10, p < 0.01) were higher in the TBT group. Removal of the endothelium was associated with an increase of Emax in the control group and an increase pD2 in the TBT group, although the magnitude of the response (analyzed by dAUC) was not different between the groups. L-NAME administration promoted an increase of Emax and pD2 to phenylephrine, both in the absence and in the presence of TBT. The magnitude of this effect was greater in the presence of TBT (dAUC % - control: 55.69 ± 12.96 vs TBT 102.70 ± 16.78 %). The vasodilation induced by ACh (Emax, Control: -105.3 ± 0.15; TBT: 91.26 ± 0.92 %, n=10; pD2, Control: -6.07 ± 0.01, n=10; TBT: -5.79 ± 0.02 %, n=10, p < 0.01) and SNP (Emax, Control: -99.37 ± 1.65, n=9; TBT: -80.68 ± 2.78 %, n=10; pD2, Control: - 7.64 ± 0.08, n=9; TBT: 3.63 ± 0.57, n=10; p < 0.01) were modified by exposure to TBT. Furthermore, exposure to TBT induced an increase in superoxide anion production "in situ" mainly in the smooth, reduction of wall thickness (Control: 133.24 ± 5.29, n=5; TBT: 87.29 ± 0.75 µm, n=5) increased collagen deposition and endothelial denudation with accumulation of red blood cells, fibrin and platelets in aortic rings. Thus, the results obtained in this study suggest that TBT causes an impaired vascular reactivity of female rats, probably due increased production of reactive oxygen species (ROS) and morphologic abnormalities.